Model Construction and Parameter Optimization of a Eight-link Mechanism with Posture Transformation of Sitting and Lying - Liu Hua; Zhang Qiuju (Jixie chuandong)
Based on the principle of human engineering,the eight-link mechanism with posture transformation of sitting and lying is designed. In order to ensure the stability of the mechanism and obtain better practical performance,the optimization design of the eight-link posture transformation mechanism is carried out.According to the process characteristic requirements,the specific constraint conditions and the optimization target of the eight-link posture transformation mechanism,the mathematical model of eight-link mechanism is constructed,the optimization design model of eight-link mechanism is established by using the ADAMS/View model,the optimization design of eight-link mechanism is carried out. From the results of the optimization design and the angle of the connecting rod,speed and acceleration curve before and after optimization,the optimization design coincides with the corresponding principle of human engineering, meeting the design requirements and purpose of the eight-link posture transformation mechanism.